TERMINATION OF ACCURATE INVESTIGATIONS AND RESTORATIVE JUSTICE - Suisno; Isnaini, Enik; Royani, Ahmad; Arifah, Nur (Jurnal Independent, 2022)
Abstraction Restorative Justice accommodates the interests of the parties, including the victim, because the victim in this case is involved in determining the sanctions for the perpetrator. Restorative Justice returns conflict to the most affected parties (victims, perpetrators and “their community”) and gives priority to their interests. Restorative justice seeks to restore the victim's safety, personal respect, dignity, and more importantly a sense of control. By adhering to the paradigm of restorative justice, it is hoped that the loss and suffering suffered by the victim and his family can be recovered and the guilt burden of the perpetrator of the crime can be reduced because he has received forgiveness from the victim or his family.